Edukasi Literasi Digital dalam Pelayanan Publik: Sosialisasi dan Pendampingan Bagi Masyarakat di Pulau Timor - Izana, Nyimas Nadya; Sabariman, Hoiril; Susanti, Anik (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Current community activities cannot be separated from the use of technology, one of which is in the field of public services at the village level. Various factors that have not been able to involve village communities in the use of digital technology in public services are still difficult to obtain information, lack of literacy, and limitations in understanding digital literacy, especially in rural areas. This community service is carried out to increase digital literacy for the village community, especially about public services. The method of implementing this service uses Participation Action Research (PAR) in the form of socialization and mentoring. Three main conclusions were obtained from this community service activity, namely; First, the Kabuna Village Community, especially the community service target, has experienced an increase in digital literacy skills. This can be seen in the ability to access public services. Second, the people of Kabuna Village gain new knowledge and experience, especially those related to administrative mechanisms. Third, the people of Kabuna Village are able to utilize the village website as one of the media to promote the values of local wisdom that develop in the community.